Biochemical characterization of bacterial isolates from eggs, larvae and postlarvae of Penaeus monodon. - Salas, Ayn Aimee Jalando-on
Characterization and identification through biochemical tests were done to bacterial isolates from eggs, larvae and postlarvae of Penaeus monodon. Five genera were identified, Vibrio spp. and aeromonas spp. being more dominant than the rest. The others include Pseudomonas spp., Escherichia spp. and Klebsiella spp.., The different stages had various bacteria preent. In the eggs onlly Vibrio sppp., Aeromonas spp. and Pseudomonas spp. were present. The mysis stage had all five genera present. In the postlarval stage only Vibrio spp., Aeromonas spp. and Klebsiella spp. were present. All five genera are known as normal microflora as well as possibe causative agents of prawn diseases.